A bomb built in hell : Wesley's story - Vachss, Andrew H. (Vintage Books, 2012)
Becoming Carmine Trentoni's hitman after emerging from prison, Wesley locates Pet and the two set up shop in Brooklyn, executing their assignments with finesse -- and occasionally, more explosives than are strictly called for. But Wesley isn't satisfied with his low-profile lot, and sets out to make a mark on the city that everyone will notice.